2019
DOI: 10.1073/pnas.1909604116
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel bacterial queuine salvage enzymes and pathways in human pathogens

Abstract: Queuosine (Q) is a complex tRNA modification widespread in eukaryotes and bacteria that contributes to the efficiency and accuracy of protein synthesis. Eukaryotes are not capable of Q synthesis and rely on salvage of the queuine base (q) as a Q precursor. While many bacteria are capable of Q de novo synthesis, salvage of the prokaryotic Q precursors preQ0 and preQ1 also occurs. With the exception of Escherichia coli YhhQ, shown to transport preQ0 and preQ1, the enzymes and transporters involved in Q salvage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 75 publications
1
61
0
Order By: Relevance
“…Q is highly conserved and found in plants, fishes, insects, and mammals. While many bacteria can synthesize queuine (the nucleobase of Q) de novo, salvaging the prokaryotic Q precursors preQ 0 and preQ 1 has recently been reported [ 62 ]. Eukaryotes are not capable of Q synthesis and they rely on salvaging the queuine base as a Q precursor either by nutrition or by the intestinal bacterial flora [ 63 , 64 , 65 ].…”
Section: Response Of E Histolytica To Os In Prmentioning
confidence: 99%
“…Q is highly conserved and found in plants, fishes, insects, and mammals. While many bacteria can synthesize queuine (the nucleobase of Q) de novo, salvaging the prokaryotic Q precursors preQ 0 and preQ 1 has recently been reported [ 62 ]. Eukaryotes are not capable of Q synthesis and they rely on salvaging the queuine base as a Q precursor either by nutrition or by the intestinal bacterial flora [ 63 , 64 , 65 ].…”
Section: Response Of E Histolytica To Os In Prmentioning
confidence: 99%
“…Eubacteria can synthesize the queuine nucleobase precursor of queuosine de novo . However, a recent study showed that some Eubacteria can also salvage precursors of queuosine ( 11 ). Since mammals cannot synthesize queuine and salvage it from diet and gut microbes, these observations suggest a dynamic supply and demand for queuine by both the gut microbiota and the host ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the availability of a nutrient varies throughout the process of gut colonization. It is therefore not surprising that many microorganisms have both a salvage and a biosynthetic pathway for a given nutrient, in order to survive in fluctuating and sometimes crowded gut environments [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%